Quichotte eaudiobook A novel. - Rushdie, Salman (Random House Audio, 2019)
NEW YORK TIMES BESTSELLER • An epic  Don Quixote  for the modern age, “a brilliant, funny, world-encompassing wonder” ( Time ) from internationally bestselling author Salman Rushdie   SHORTLISTED FOR THE MAN BOOKER PRIZE • “Lovely, unsentimental, heart-affirming . . . a remembrance of what holds our human lives in some equilibrium—a way of feeling and a way of telling. Love and language.”—Jeanette Winterson, The New York Times Book Review NAMED ONE OF THE BEST BOOKS OF THE YEAR BY TIME AND NPR Inspired by the Cervantes classic, Sam DuChamp, mediocre writer of spy thrillers, creates Quichotte, a courtly, addled salesman obsessed with television who falls in impossible love with a TV star. Together with his (imaginary) son Sancho, Quichotte sets off on a picaresque quest across America to prove worthy of her hand, gallantly braving the tragicomic perils of an age where “Anything-Can-Happen.” Meanwhile, his creator, in a midlife crisis, has equally urgent challenges of his own. Just as Cervantes wrote Don Quixote to satirize the culture of his time, Rushdie takes the reader on a wild ride through a country on the verge of moral and spiritual collapse. And with the kind of storytelling magic that is the hallmark of Rushdie’s work, the fully realized lives of DuChamp and Quichotte intertwine in a profoundly human quest for love and a wickedly entertaining portrait of an age in which fact is so often indiscernible from fiction. Praise for Quichotte “Brilliant . . . a perfect fit for a moment of transcontinental derangement.” — Financial Times “ Quichotte  is one of the cleverest, most enjoyable metafictional capers this side of postmodernism. . . . The narration is fleet of foot, always one step ahead of the reader—somewhere between a pinball machine and a three-dimensional game of snakes and ladders. . . . This novel can fly, it can float, it’s anecdotal, effervescent, charming, and a jolly good story to boot.” — The Sunday Times “ Quichotte  [is] an updating of Cervantes’s story that proves to be an equally complicated literary encounter, jumbling together a chivalric quest, a satire on Trump’s America and a whole lot of postmodern playfulness in a novel that is as sharp as a flick-knife and as clever as a barrel of monkeys. . . . This is a novel that feeds the heart while it fills the mind.” — The Times  (UK)